The effectiveness of STEAM technologies on improving the professional competence of natural science students - Zhusupkalieva, Galiya; Kuanbayeva, Bayan; Rakhmetov, Maxot; Saltanova, Galiya; Kuzmicheva, Alexandra; Tumysheva, Anar (Frontiers in Education, 2025)
IntroductionSTEAM technologies make it easier to use professional skills by combining an interdisciplinary approach to learning. The study problem concerns the absence of specialized approaches to learning physics using STEAM technologies that would enable a rethinking of how professional knowledge is acquired. The goal of this work is to check out the benefits of STEAM technologies in boosting the professional skills of natural science students.MethodsThe study employed modeling, comparison, survey methods, TOWS analysis, Student's t-test, and McNemar's test. To achieve the research objective, 71 students preparing to become physics teachers were involved.Results and discussionDuring the training, the use of digital platforms PhET Interactive Simulations and Khan Academy, group learning and student modeling of educational topics were provided for. The key results consisted in improved student performance attributable to the use of STEAM technologies. This was manifested in an improvement in theoretical knowledge from 4.2 points to 4.6 points; practical knowledge from 3.8 points to 4.8 points; and project activity from 3.5 points to 4.8 points. It was found that the skills obtained by students were characterized by the formation of critical thinking and creative skills. In solving situational problems using STEAM technologies, the greatest advantage was associated with the use of an interdisciplinary approach (28%), flexibility in processing information (26%). TOWS analysis made it possible to determine the primary influence of STEAM education on solving professional tasks. The practical significance of the article is related to improving the professional competence of future teachers through the use of STEAM technologies.